The Use of Digital Illustrators in Histology Practicum Learning of Medical Students In Gorontalo: Perception Study - Alian Ridho; Fatra Fasya Gusasi; Abdi Dzul Ikram Hasanuddin; Sri A Ibrahim (Universitas Negeri Gorontalo, 2022)
Introduction: Medical students need to learn histology to understand the relation between microscopic structure and function of cells and tissues. Pictures of manual preparation made by students can be used as notes and can describe students' understanding of the observed structures. Producing good pictures in a short time is a challenge for medical students. The use of digital illustrator technology is expected to be a solution to overcoming these problems. This study aims to measure the perception of acceptance and satisfaction rate of medical students in Gorontalo towards digital illustrators in apprehend histology practicum.Method: Cross-sectional descriptive survey with modified questionnaires from previous studies. The sampling technique used purposive sampling and involved 54 first-year students. The raw data were analyzed using Microsoft Excel. The mean value calculated for each item was compared with the theoretical mean value of 2.50 to determine whether the respondents agreed with the statement.Results: All items have an average rating exceeding the theoretical mean of 2.50. Also, the mean of 3.91 (SD = 0.58) for all items substantially exceeds the theoretical mean. Items with the highest perceived rate of perceived utility, ease of use, intention to use, and actual use of digital illustrator teaching materials in learning practical skills will significantly increase students' motivation, interest, and acquisition of practical skills.Conclusion: the use of digital illustrators is perceived positively by medical students in helping histology practicum learning, which is indicated by the high rate of acceptance and rate of satisfaction with its use.